The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1263/jbb.93.95
|View full text |Cite
|
Sign up to set email alerts
|

Production of .GAMMA.-Aminobutyric Acid from Alcohol Distillery Lees by Lactobacillus brevis IFO-12005.

Abstract: Lactobacillus brevis IFO-12005 showed good growth in rice shochu distillery lees (kome shochu kasu). Almost all of the free glutamic acid (10.50 mM) in shochu kasu was converted to gamma-amino-butyric acid (GABA) within 2 d of stationary culture at 30 degrees C. The amount of GABA in the kome shochu kasu medium finally reached 10.18 mM. After centrifugation of the broth culture, the supernatant fraction was treated with a flocculation agent to form a clear solution, then passed through a column containing a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…GABA production by microbes has been examined mainly for Lactobacillus, [28][29][30][31][32] but only a few experiments have been carried out on yeast. 23) We found that four out of 13 isolates screened, including Hachinohe No.…”
Section: Discussionmentioning
confidence: 99%
“…GABA production by microbes has been examined mainly for Lactobacillus, [28][29][30][31][32] but only a few experiments have been carried out on yeast. 23) We found that four out of 13 isolates screened, including Hachinohe No.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14]16) In the Enterococcus strains, E. casseliflavus has been only reported to be the GABA-producing strain. 15) In this study, we found that E. avium G-15 from carrot leaves has high potency for GABA production.…”
Section: Discussionmentioning
confidence: 99%
“…There is no detailed report about L. fermentum mediated GABA production. A previous report by Yokoyama et al (2002) has enlightened the use of L. brevis for the production of γ-aminobutyric acid from the residue of alcohol distillery. A study has reported the cloning and expression of GAD from L. brevis OPK-3 in E. coli (Park & Oh, 2007), but the enzyme was unstable.…”
Section: Bacterial Identificationmentioning
confidence: 99%
“…Komatsuzaki et al (2005) have reported the ability of L. paracasei to produce GAD isolated from traditional fermented foods. A study by Yokoyama et al (2002) explains the use of L. brevis IFO-12005 for the production of γ-aminobutyric acid from the residue of alcohol distillery. Recently, a study has reported that L. reuteri 100-23 play a role in acid resistance during fermentation owing to the production of GAD (Su et al, 2011).…”
Section: Introductionmentioning
confidence: 99%